Looking Beyond Risk in Paroling Denying Prisoners: A Response to Assy and Menashe's "The Catch-22 in Israel's Parole Law". (August 2015) - Dagan, Netanel
This paper offers an additional theoretical perspective to the "Catch-22" problem as discussed in Assy and Menashe's article, which appeared in the December 2014 issue of Criminal Justice and Behavior . It offers to look beyond risk in the discussion about parole of denying prisoners. By focusing on the retributive meaning of the problem, the paper offers an additional framework to discuss the magnitude of the problem (via proportionality analysis), and the overt and covert forces that influence a parole board's discretion in action (via character retributivism analysis).